Isolation of different fungi from the skin of patients with seborrheic dermatitis - Elaheh Mahmoudi; Jahangir Rezaie (Mazandaran University of Medical Sciences, 2020)
Background and Purpose: Seborrheic dermatitis (SD) is characterized by erythematous inflammatory patches that mostly appear in the sebaceous gland-rich skin areas. In addition to the key role of Malassezia species in SD, its contribution to other fungal microbiota has been recently addressed in the literature. Regarding this, the present study was conducted to identify and determine the fungal species associated with the incidence of SD. Materials and Methods: For the purpose of the study, fungal microbiome in scaling samples were collected from SD lesions and then analyzed based on the DNA sequencing of ITS regions. Results: In addition to Malassezia, several fungal species were detected in the samples collected from the SD lesions. According to the results, 15.5%, 13.3%, and 6.7% of the isolates were identified as Candida parapsilosis, Cryptococcus albidus var. albidus/ Rhodotorula mucilaginosa, and Penicillium polonicum, respectively. Conclusion: Based on the obtained results, C. parapsilosis was the most prevalent non-Malassezia species isolated from SD lesions. Our results provided basic information about a specific fungal population accounting for the incidence of SD.